New Metal(II) Complexes of 2-Hydroxy-N-(2-Hydroxynaph Thalene-1-yl) Methylene Benzohydrazide: Synthesis and Spectroscopic Studies - ظفر توفیق; ماهر الطائی (University of Mosul-college of Basic Education, 2023)
The study includes the preparation of complexes Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Hg(II) with Schiff base ligand (HNMBH2) which is derived from the condensation reaction of 2-hydroxybenzohydrazide with 2-Hydroxy-1-naphthalene carboxaldehyde. The properties of which were characterized by infrared, magnetic measurements, molar conductivity measurements, electronic spectra, nuclear magnetic resonance spectra of 1H and13 C, and gas chromatography-mass spectrometry. It is found  that the ligand acts as neutral tridentate to give high-stability mononuclear complexes that have a tetrahedral or square planar structure.